Resistance to Post-Disaster Planning: Strategies of the Third Sector in the Reconstruction of San Juan, Argentina, after the 1944 Earthquake. (Res Gesta, 2025)
On 15 January 1944, an earthquake destroyed the city of San Juan and its surrounding areas, creating the need to design an entirely new urban fabric. Building on previous research, this article analyses the conflicts surrounding San Juan’s reconstruction by examining the claims put forward by different social sectors that resisted the official proposals. In particular, it explores the positions adopted by the Unión Vecinal de Villa Krause, the Unión Vecinal de Concepción, and the Federación Obrera Sanjuanina (FOS) in response to a series of building and urban issues raised by the technical bodies involved in the process, with the aim of foregrounding the role of the third sector. We approach this case as a way of bringing to light —through a historical perspective— the actions of an actor frequently overlooked in disaster contexts. We show that, although disregarded both in their own time and in historiography, third-sector actors developed various strategies to articulate their aspirations and demands throughout the reconstruction process.
Keywords: Reconstruction; Disasters; Third sector; San Juan